Natural Clinopyroxene Reference Materials for in situ Sr Isotopic Analysis via LA-MC-ICP-MS - Zhao, Han; Zhao, Xin-Miao; Le Roux, P. J.; Zhang, Wen; Wang, Hao; Xie, Lie-Wen; Huang, Chao; Wu, Shi-Tou; Yang, Jin-Hui; Wu, Fu-Yuan; Yang, Yue-Heng (Frontiers in Chemistry, 2020)
Clinopyroxene is a major host mineral for lithophile elements in the mantle lithosphere, and therefore, its origin is vital for constraints on mantle evolution and melt generation. In situ Sr isotopic measurement of clinopyroxene has been available since the recent development of laser ablation multicollector inductively coupled plasma mass spectrometry (LA-MC-ICP-MS) in the 2000s. Therefore, there is an increasing demand for natural clinopyroxene reference materials for Sr isotope microanalysis. In this contribution, we present six natural clinopyroxene reference materials from South Africa (JJG1424) and China (YY09-47, YY09-04, YY09-24, YY12-01, and YY12-02) for Sr isotope microanalysis. The Sr content of these clinopyroxenes ranges from 50 to 340 μg g−1, which covers most natural clinopyroxene compositions. Homogeneity of these potential reference materials were investigated and evaluated in detail over a 2-year period using 193-nm nanosecond and 257-nm femtosecond laser systems coupled to either a Neptune or Neptune Plus MC-ICP-MS. Additionally, the major and trace element of these clinopyroxenes were examined by electron probe microanalyzer (EPMA) as well as solution and laser ICP-MS. The in situ87Sr/86Sr values obtained for the six natural clinopyroxene reference materials agree well with data obtained using the thermal ionization mass spectrometer (TIMS) method. The Sr isotopic stability and homogeneity of these clinopyroxenes make them potential reference materials for in situ Sr microanalysis to correct instrumental fractionation or as quality control materials for analytical sessions. The new Sr isotope data provided here might be beneficial for microbeam analysis in the geochemical community.